Distribution of power : choosing the system of governance in the reform of the Jamaican constition. - SEAGA, Edward (1997)
Assesses alternative systems of government and concludes that one system is the most effective and least susceptible to abuse - provided certain new procedures and attitudes also emerge from Jamaica's constitutional review.